Arms up vs. arms down: CT dose optimization - Borlinhas, Filipa (2017)
Introduction - Computed Tomography (CT) technologies are evolving in terms radiation dose optimization. When a transition of CT technology takes place, every procedure should be revised and questioned in terms of radiation dose optimization. A procedure such as positioning a patient for a CT examination may be considered simple, but it may become radical concerning radiation dose. The CT examination of Neck+Thorax+Abdomen+Pelvis (NTAP) requires a large anatomical region to be irradiated and, in most of the cases, the patients have to be scanned regularly to evaluate oncologic disease. Radiographers gathered efforts in order to optimize the delivered radiation dose of this type of examinations, and positioning of the patient during the scout was found as a dose reduction parameter. The aim of this work is to emphasize the need to constantly revise CT examination protocols and clinical practice. Methods - Two different positioning to perform the NTAP CT examination scout were tested, one with a patient with arms up and the other with arms down. In the past, these examinations were performed with arms down so it was only necessary to do the new CT examination scouts with arms up. Dose estimations provided by the CT equipment were reported and compared between the two different positioning during the scout. Results - The radiation dose for the entire NTAP examination was lower when the scout was performed with arms up. Considering AEC technology, contrast media phases, anatomical regions specificities, and patient comfort, these tests were performed without compromising the diagnosis of the patient, but significant changes had to be applied to the protocol. Conclusions - The CT technology evolution implies changes in clinical practice and examination procedures. It is extremely important that the Radiology professionals revise their practices periodically in order to find procedures that can be optimized in terms of radiation dose.